Odpowiedzi

Najlepsza Odpowiedź!
2010-04-13T15:54:29+02:00
A) 0,5(2-4x) = 3 - x
1-2x = 3 - x
-2x +x = -1 + 3
-x = 2 | : (-1)
x= -2

b) 2(x-4) = -2 ( 2+x)
2x - 8 = -4 - 2x
2x + 2x = 8 - 4
4x = 4 | : 4
x = 1

c) (1+x) - (2+3x) = 0
1 + x - 2 - 3x = 0
-1 - 2x = 0
-2x = 1 + o
-2x = 1 | : (-2)
x = - 0,5

d) 2(x-4)=-(3x + 2)
2x - 8 = -3x - 2
2x + 3x = 8 - 2
5x = 5 | :5
x = 1

e) 1/2x +(1/2x - 2)=2
1/2x +1/2x - 2 = 2
x - 2 = 2
x = 4

f) 3x -(x+2) = x+3
3x - x - 2 = x + 3
2x - 2 = x + 3
2x - x = 2 +3
x = 5


p. s. powinno byc dobrze